Revisiting Legal Policy Effectiveness: Governance Mechanisms and Persistent Social Inequality - Mukhlisin, Mukhlisin; Hakim, Arif Rohman; Hidayat, Agus Rohmat (Politeknik Siber Cerdika Internasional, 2024)
Background: This study explores the relationship between legal policy frameworks, governance mechanisms, and social inequality across socio-economic contexts. Despite significant policy reforms aimed at reducing inequality in the past two decades, many societies still face substantial disparities. Objective: The study aims to explore the gaps between policy formulation and its impact on reducing inequality, focusing on governance quality and contextual influences. Methods: A mixed-methods approach was employed, combining quantitative analysis of policy effectiveness indices from 124 countries (2015-2025) and qualitative assessments of governance structures in 12 case studies. The quantitative component examined the relationship between governance quality and policy effectiveness, while qualitative case studies assessed governance dynamics and contextual factors. Results: The findings reveal that governance quality significantly influences policy effectiveness. Countries with higher governance quality scores (above 7.0) reduced inequality by 45% more effectively than those with lower scores (below 5.0). Contextual factors, including political stability, socio-cultural dynamics, and resource availability, were found to significantly influence the effectiveness of governance in reducing inequality. Regulatory compliance mechanisms (impact score: 7.8/10) and policy coherence (7.5/10) were most effective, while resource allocation (5.9/10) was the weakest link. Conclusion: The study introduces an analytical framework linking legal policy, governance, and context. It highlights that effective inequality reduction requires well-designed policies and adaptive governance systems responsive to local contexts. Policymakers should prioritize strengthening institutional capacity, monitoring systems, and inclusive stakeholder participation.